The Roman Sacred Music of Alessandro Scarlatti - Della Libera, Luca (Oxon New York Routledge, 2022)
This book offers an account of the sacred music written by Alessandro Scarlatti (1660–1725) in Rome, a city where the composer lived and worked for many years throughout his career. Using archival research, Luca Della Libera provides an overview of Scarlatti’s life and activities in Rome, addresses his connections with the institutions and patrons of the city, and analyses his Roman repertoire in comparison to the sacred music of other contemporary composers, demonstrating its unique characteristics. An appendix includes transcriptions of the archival sources connected with Scarlatti’s activity in Rome. The first major publication in English to address the sacred music repertoire of one of the major composers of the Italian Baroque, this book offers new insights into Scarlatti’s work and a valuable resource for researchers in musicology and early modern studies.
Introduction Part I Scarlatti and the Eternal City: 1 The Roman Scene -- 2. Biography Part II The Repertoire: 3. Music for the Sistine Chapel and Cardinal Ottoboni -- 4. Music for Santa Maria Maggiore -- 5. Music on commission -- 6. Music for the Basilica of Santa Cecilia in Trastevere Conclusion
Keywords: Scarlatti, Alessandro -- 1660-1725; 17th Century (1601-1700); 18th Century (1701-1800); Church music; Mass; Rome (Italy)